Manipulation of electron deficiency of δ-carboline derivatives as bipolar hosts for blue phosphorescent organic light-emitting diodes with high efficiency at 1000 cd m−2. Issue 19 (13th April 2016) - Zhang, Zhen; Xie, Jingwei; Wang, Zixing; Shen, Bowen; Wang, Hedan; Li, Minjie; Zhang, Jianhua; Cao, Jin
Abstract : Structure–property relationship of pyridine-modified δ-carboline derivatives as bipolar hosts for highly efficient blue OLED. Abstract : The effect of different linkages on thermal, electrochemical, photophysical, and optoelectronic properties was discussed in detail to illuminate the structure–property relationship of four δ-carboline derivatives, 5-(3′-(9 H -carbazol-9-yl)-[1, 1′-biphenyl]-3-yl)-5 H -pyrido[3, 2- b ]indole (CzBPDCb ), 3, 3′-bis(5 H -pyrido[3, 2- b ]indol-5-yl)-1, 1′-biphenyl (BDCbBP ), 5-(5-(3-(9 H -carbazol-9-yl)phenyl)pyridin-3-yl)-5 H -pyrido[3, 2- b ]indole (Cz35PyDCb ), and 5-(6-(3-(9 H -carbazol-9-yl)phenyl)pyridin-2-yl)-5 H -pyrido[3, 2- b ]indole (Cz26PyDCb ). Their triplet energies ( E T = 2.78–2.96 eV) and the lowest unoccupied molecular orbital (LUMO) energy could be manipulated by the linkage and the number of δ-carboline units. These materials exhibited bipolar features with good hole- and electron-transporting properties. These host materials when doped with bis(3, 5-difluoro-2-(2-pyridyl)phenyl-(2-carboxypyridyl)iridium(iii )) (FIrpic) demonstrated efficient blue phosphorescent organic light emitting diode (OLED) with reduced driving voltage, high efficiency, and negligible roll-off. Among these four materials, Cz35PyDCb performed as a host material for blue OLED with ideal current and power efficiencies (CEmax at 44.7 cd A −1, and PEmax at 40.2 lm W −1 ), as well as good external quantum efficiency (EQEmax at 22.3%). Most importantly, at the normal 1000 cd m −2 operation brightness, the efficiencies remained at 42.6 cd A −1 for CE (95% of CEmax ), 31.7 lm W −1 for PE (79% of PEmax ), and 20.1% for EQE (90% of EQEmax ), which indicated well-balanced carriers transporting and good confinement of the triplet excitons in the emitting layer, even at high current density. Moreover, introduction of the δ-carboline moiety could improve the thermal and morphological stabilities.